Enabling the seamless coordination and synchronization of microgrids using batteries - Morán Río, Diana Patricia; Roldan Perez, Javier; Prodanovic, Milan; García Cerrada, Aurelio (My University, 2025)
Microgrids (MGs) have become a commonly used way for renewable energy sources (RESs) integration in electrical distribution systems. These MGs are formed of a mix of RESs and batteries that can operate either in grid-forming or grid-following control modes. In these new scenarios, the transition from islanded to grid-connected mode is a challenging issue, especially if there are renewable-based grid-forming converters working at their maximum power point. In this paper, a secondary controller that enables the seamless operation of grid-forming converters with batteries is proposed. This controller allows the connection of loads and synchronisation of the MG with the main grid without the need for altering the power injected by some selected grid-forming converters (e.g., those working at their maximum power point). Meanwhile, any additional power demand is met by the batteries and shared between them according to their SoC. The main developments are tested using Simulink and simPowerSystems simulation environments.